Exploring Factors Influencing the Adoption of Online Shopping: A Qualitative Approach (Journal of Informatics Education and Research, 2024)
This research explores the leading indicators that influence the adoption of electronic shopping using a qualitative method, with the purpose of understanding consumer behavior in the digital marketplace. 30 participants were interviewed, making for a diverse demographic in a bid to ensure profound revelations. The findings indicate that factors such as perceived ease of use comprise 78%, trust entails 82%, convenience forms 74%, and social influence accounts for 68% as the most important determining indicators of online shopping adoption. Demographic variables, including age and technological competence, were recognized as significant determinants, with younger, more technologically adept consumers demonstrating a greater inclination toward engaging in online shopping (88%). The findings suggest that trust, especially concerning security issues and prior experiences, is pivotal in fostering online shopping behavior. The results of this research are consistent with the current body of literature, underscoring the significance of variables such as user-friendliness and trustworthiness in multiple digital environments. This study enhances the comprehension of the consumer decision-making process and offers practical recommendations for enterprises aiming to refine their e-commerce platforms. Businesses may utilize these insights to enhance user experiences, foster trust, and advance marketing approaches, thereby promoting greater consumer engagement and loyalty.